Insect Mating Behaviors: A Review of the Regulatory Role of Neuropeptides - Alfayo Ombuya; Jianyang Guo; Wanxue Liu (Insects)
Insect mating behaviors are complex, diverse, and primarily regulated by neuropeptides and their receptors. Neuropeptides are peptide signaling molecules mainly secreted by insects’ central nervous system (CNS) to reach target organs. A substantial body of research on the role of neuropeptides in regulating mating behaviors in insects has been undertaken. This review aims to (1) synthesize existing knowledge on insect mating behaviors, (2) elucidate the neuropeptidergic mechanisms governing these behaviors, and (3) identify knowledge gaps and propose future research directions. The mating process, covering mate attraction, courtship rituals, copulation, and post-mating behaviors, was elucidated with appropriate examples. Additionally, specific neuropeptides involved at each stage of the mating process, their functions, and mechanistic aspects were discussed as demonstrated in research. The review highlights that insects display behavioral dimorphism in the mating process driven by a complex underlying neuropeptidergic mechanism. While previous publications have generally addressed the role of neuropeptides in insect behavior, none has intensively and methodically examined their role in mating behaviors. In this review, we synthesized 18 neuropeptides that we found to regulate mating behaviors in insects. We note that some of the neuropeptides are malfunctional in their regulatory roles, while others are specific. We also note that these neuropeptides execute their regulatory functions through the G protein-coupled receptor (GPCR) signaling pathway but may take different routes and messengers downstream to effect behavioral change. Neuropeptides also interact with other regulatory systems, such as the endocrine system, to discharge their functions. Given their significance in mediating mating and reproduction, targeted manipulation of the signaling system of neuropeptides could serve as viable targets in the production of ecologically friendly pest management tools. Tools that could disrupt the mating process would be applied in crop production systems to reduce the population pressure of destructive pests, consequently reducing the urge to use chemical pesticides that are ecologically unfriendly. Our findings not only advance the understanding of neuropeptide-mediated mating regulation but also highlight their potential as eco-friendly pest control targets.